Предмет: Алгебра,
автор: savanovicsasa28
помогите
1) (3+х)*(х-3)-(3-х) во 2 степени
2) (2х-4) во 2 степени-(2з+3) во 2 степени
Ответы
Автор ответа:
1
Объяснение:
1) (3+х)*(х-3)-(3-х)² = х²-9-(9-6х+х²)=х²-9-9+6х-х²=-18+6х
2) (2х-4)²-(2з+3)²=4х²-16х+16-(4з²+12з+9)=
=4х²-16х+16-4з²-12з-9=4х²-16х+5-4з²-12з
Похожие вопросы
Предмет: Русский язык,
автор: galka2010
Предмет: Английский язык,
автор: MrGospodin
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: LiveSosa
Предмет: Химия,
автор: Аноним